2017
DOI: 10.1159/000480247
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment Serum Carbohydrate Antigen 19-9 Concentration Is a Predictor of Survival of Patients Who Have Undergone Curative Resection of Stage IV Rectal Cancer

Abstract: Background: To evaluate whether pretreatment carcinoembryonic antigen and carbohydrate antigen (CA)19-9 are useful predictors of survival in patients with stage IV rectal cancer who have undergone curative resection. Methods: In this retrospective study, data on 73 patients who had undergone curative resection of stage IV rectal cancer were reviewed. Associations between various clinicopathological factors and survival outcomes were analyzed. Results: According to univariate analysis, elevated pretreatment CA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The tumour markers CEA and CA19‐9 are common indicators for preoperative early diagnosis, treatment monitoring and postoperative follow‐up, but their prognostic performance in patients with LARC undergoing nCRT remains under investigation. At present, elevated serum CEA has been classified into category I according to the strength and reliability of the published evidence in the literature, and the prognostic significance of CA19‐9 has also been confirmed by an increasing number of studies [11,12,18], including our previous research [11]. However, most previous studies only analysed single tumour markers and mainly focused on the pretreatment level [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The tumour markers CEA and CA19‐9 are common indicators for preoperative early diagnosis, treatment monitoring and postoperative follow‐up, but their prognostic performance in patients with LARC undergoing nCRT remains under investigation. At present, elevated serum CEA has been classified into category I according to the strength and reliability of the published evidence in the literature, and the prognostic significance of CA19‐9 has also been confirmed by an increasing number of studies [11,12,18], including our previous research [11]. However, most previous studies only analysed single tumour markers and mainly focused on the pretreatment level [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Whether CEA, CA199 levels, and MTL could serve as a predictor of LN metastasis remains controversial, possibly due to the heterogeneous populations of rectal cancer patients across different studies. Several studies have reported no associations between CEA, CA199 levels, MTL, and LN status (28-30), while others found that they were preoperative predictors of LN metastasis (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CA 19-9 is another widely used tumor marker in gastrointestinal tumor and is a significant predictor of survival for rectal cancer 3032. However, few studies analyzed the association between CA19-9 and nCRT response.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, CA 19-9 is another widely used tumor marker in gastrointestinal tumor and is a significant predictor of survival for rectal cancer. 30 32 However, few studies analyzed the association between CA19-9 and nCRT response. Our study suggested that pretreatment CA19-9 and pre–post-CA19-9 ratio were significantly associated with stage ypT0-2N0 tumor, and pre–post-CA19-9 ratio was significantly associated with pCR.…”
Section: Discussionmentioning
confidence: 99%